Long Non-coding RNA XIST Attenuates Diabetic Peripheral Neuropathy by Inducing Autophagy Through MicroRNA-30d-5p/sirtuin1 Axis - Liu, Bei-Yan; Li, Lin; Bai, Li-Wei; Xu, Chang-Shui (Frontiers in Molecular Biosciences, 2021)
Diabetic peripheral neuropathy (DPN) is a prevalent diabetes mellitus [1] complication and the primary reason for amputation. Meanwhile, long non-coding RNAs (lncRNAs) are a type of regulatory non-coding RNAs (ncRNAs) and broadly participate in DPN development. However, the correlation of lncRNA X-inactive specific transcript (XIST) with DPN remains unclear. Here, we were interested in the role of XIST in the modulation of DPN progression. Significantly, our data showed that the XIST and sirtuin1 (SIRT1) expression were inhibited and the microRNA-30d-5p (miR-30d-5p) expression was enhanced in the trigeminal sensory neurons from diabetic mice compared with the normal mice. The levels of LC3II and Beclin-1 were inhibited in the diabetic mice. The treatment of high glucose (HG) reduced the XIST expression in Schwann cells. The apoptosis of Schwann cells was enhanced in the HG-treated cells, but the overexpression of XIST could block the effect in the cells. Moreover, the levels of LC3II and Beclin-1 were reduced in the HG-treated Schwann cells, while the overexpression of XIST was able to reverse this effect. The HG treatment promoted the production of oxidative stress, while the XIST overexpression could attenuate this result in the Schwann cells. Mechanically, XIST was able to sponge miR-30d-5p and miR-30d-5p targeted SIRT1 in Schwann cells. MiR-30d-5p inhibited autophagy and promoted oxidative stress in HG-treated Schwann cells, and SIRT1 presented a reversed effect. MiR-30d-5p mimic or SIRT1 depletion could reverse XIST overexpression-mediated apoptosis and autophagy of Schwann cells. Thus, we concluded that XIST attenuated DPN by inducing autophagy through miR-30d-5p/SIRT1 axis. XIST and miR-30d-5p may be applied as the potential targets for DPN therapy.